Medieval archaeology : understanding traditions and contemporary approaches - Gerrard, Christopher M. (Routledge, 2002)
Chris Gerrard looks at the people and excavations that have been important in medieval archaeology and the core theory and methodology used, creating an essential text for all medieval archaeologists.